20‐month‐olds selectively generalize newly learned word meanings based on cues to linguistic community membership. Issue 4 (27th January 2022) - Weatherhead, Drew; Werker, Janet F.
Abstract: A growing body of work suggests that speaker‐race influences how infants and toddlers interpret the meanings of words. In two experiments, we explored the role of speaker‐race on whether newly learned word‐object pairs are generalized to new speakers. Seventy‐two 20‐month‐olds were taught two word‐object pairs from a familiar race speaker, and two different word‐object pairs from an unfamiliar race speaker (four new pairs total). Using an intermodal preferential looking procedure, their interpretation of these new word‐object pairs was tested using an unpictured novel speaker. We found that toddlers did not generalize word meanings taught by an unfamiliar race speaker to a new speaker (Experiment 1), unless given evidence that the unfamiliar race speaker was a member of the child's linguistic community through affiliative behaviour and linguistic competence (Experiment 2). In both experiments, generalization was observed for the word‐object pairs taught by the familiar race speaker. These experiments indicate that children attend to speakers' non‐linguistic properties, and this, in turn, can influence the perceived relevance of speakers' labels. Abstract : We measured whether toddler's selectively generalize newly learned word labels on the basis of cues to linguistic community membership. In Experiment 1, toddlers generalized word‐object pairs taught by a familiar race speaker to a novel voice at test, but not word‐object pairs taught by an unfamiliar race speaker. In Experiment 2, toddlers first saw a pre‐familiarization in which both speakers were shown to be competent speakers of English and were shown to affiliate. In this case, toddlers generalized wordobject pairs taught by both speakers to a novel voice at test.